2002
DOI: 10.1001/archinte.162.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cardiorespiratory Endurance Following 6 Months of Resistance Exercise in Elderly Men and Women

Abstract: Significant improvements in aerobic capacity and treadmill time to exhaustion can be obtained in older adults as a consequence of either high- or low-intensity resistance exercise. These findings suggest that increased strength, as a consequence of resistance exercise training, may allow older adults to reach and/or improve their aerobic capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 29 publications
5
80
0
16
Order By: Relevance
“…Additionally, six of nine studies [4,9,18,21,24,33,39,49,53] in older subjects have reported significant improvements in VO 2 max following RT ( Table 2).…”
Section: Older Subjectsmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, six of nine studies [4,9,18,21,24,33,39,49,53] in older subjects have reported significant improvements in VO 2 max following RT ( Table 2).…”
Section: Older Subjectsmentioning
confidence: 97%
“…Furthermore, VO 2 max tended to increase by 5 % (0.14 % per session) after the training. On the other hand, Vincent et al [49] reported that a single set of RT at 80 % 1RM (3 days per week) for 24 weeks elicited significant increases in VO 2 max (20 %). These results suggest that training volume is not largely related to the improvement of VO 2 max for older people.…”
Section: Effects Of Training Volumementioning
confidence: 98%
See 1 more Smart Citation
“…Nesse sentido, pesquisas com idosos, observaram que o treinamento de força acarreta adaptações positivas na resistência aeróbica e força muscular 14,21,22 , e que a melhora na força muscular pode interferir nas Tabela 2. Valores da média e desvio-padrão das variáveis relacionadas ao desempenho aeróbico; das medidas dos músculos vasto lateral e reto femoral (em milímetros) e força de preensão (em 10.KGF) das participantes por grupo, pré e pós os programas de treinamentos.…”
Section: Discussionunclassified
“…Foram realizadas de oito a dez repetições para cada exercício, as cargas foram adequadas na primeira, terceira e sétima semana de treinamento; a velocidade do movimento foi de baixa a moderada intensidade, sempre sob controle; a respiração foi orientada para ser contínua durante cada repetição, expirando ao se levantar a carga e inspirando ao se abaixar a carga 14 . Cada sessão do treinamento foi composta pelos seguintes exercícios: leg press (extensão do quadril e extensão do joelho), mesa extensora (extensão dos joelhos); flexão dos joelhos (com caneleiras na posição ortostática), abdução e adução de quadril.…”
Section: Métodosunclassified